Esquizofrenia e participação social: a percepção do portador em relação ao estigma e discriminação - Pimentel, Fernanda de Almeida [UNIFESP] (2010)
Studies show attitudes and discriminatory behaviors of the general population in relation to people who have schizophrenia. Moreover, anticipated discrimination and self stigma lead to feelings of devaluation, and contribute for a negative perception of themselves and their illness leading to increased isolation and poor self esteem. Stigma and discrimination harm the users´ life and have negative effects in their social participation. Objective: To examine the phenomenon of discrimination, both experienced and anticipated, in the everyday life of people who have schizophrenia. Methods: The study was carried out in São Paulo, with 50 users at the Schizophrenia Program (PROESQ) of the Federal University of São Paulo and at the Orientation Services in Schizophrenia (S.O.eSq.) of the Brazilian Schizophrenia Association (ABRE). Study design: A transversal cohort with a convenience sample, through the application of a semistructured questionnaire “Discrimination and Stigma Scale – DISC-10, developed by Thornicroft et al. (2009), translated to Portuguese and culturally adapted to Brazilian socio-cultural reality. The scores for the analysis of the answers of the questionnaire were divided according to the categories of lived discrimination perceived as disadvantageous, indifferent, and advantageous, and of the presence or the absence of anticipated discrimination and self stigma. Results: People with schizophrenia perceived their experience of lived discrimination as indifferent more than disadvantageous or advantageous. Negative discriminatory attitudes (disadvantageous) were perceived mainly as a result of having the diagnosis of schizophrenia, in their relationship with relatives and in making or maintaining friends. Experiences of positive discrimination (advantageous) were rare. People with schizophrenia who had been involuntarily admitted do hospital, in the majority of situations, perceived their experiences of discrimination as disadvantageous. In relation to anticipated discrimination and self stigma, users reported having experienced it in association with feeling the need to hide the diagnosis of the mental illness, giving up to competing or in applying for work, apprenticeship or study, giving up searching for a relationship or in keeping an intimate relationship, and in giving up doing something important due to the diagnosis of mental illness. Users who have been involuntarily admitted a psychiatric hospital felt more disrespected, humiliated or punished in their contact with mental health professionals. However, they didn’t experience in any aspect, a denial of the social benefits or social security that they were entitled to. Moreover, users that felt disrespected, humiliated or punished in their contact with mental health professionals described more experiences of disadvantageous discrimination. The study found a positive association between the presence of anticipated discrimination and self stigma and the experience of discrimination felt as disadvantageous. Being involuntarily admitted to a psychiatric hospital increased almost seven times the chance of the discrimination experienced as disadvantageous. Conclusions: We found that users perceive stigmatized and discriminatory attitudes in several domains of life and experiment self stigma, and that these experiences have a negative impact in their opportunities of social participation. The present study contributes to affirm the importance of the users` view in the planning of actions to address these issues, having them as active participants in such process.